(untitled) (Indian Journal of Public Health Research & Development, 2024)
Fascioliasis is an often-neglected zoonotic disease caused by liver fluke Fasciola hepatica and Fasciolagigantica(1). The life cycle of this parasite starts when eggs in mammalian stool are deposited in tepid water (22-26°C) and hatch in within two weeks, miracidia appear and develop. These miracidia invade many species of freshwater snails, in which they further develop to sporocyst and redia for 4-7 weeks. They leave as free-swimming single tailed cercaria that subsequently attach to watercress, water lettuce, mint, parsley, or khat (2, 3). They encyst within few hours and wait to be eaten by the definite host, humans (4). The metacercariae exist in the small intestine is releasing the young parasites, which rapidly penetrate the intestinal wall and enter the peritoneal cavity. The immature flukes penetrate the capsule of Glisson after 48h and enter the liver then migrate throughout the hepatic parenchyma till they reach the biliary system where they become adults within 3 to 4 months from the initial infection and lay eggs (4). World health organization now recognizes human Fascioliasis as a significant public health problem and a neglected tropical disease with a great impact on human development (4). The burden of infection is unclear, and studies have shown the geographic expansion of fascioliasis in human and livestock likely related to climate change (5).This study aims to highlight the sociodemographic characteristics of human fascioliasis in a newly emerged endemic area at north of Iraq.